Verbes supports complexes et actualisation des prédicats nominaux: approche contrastive - Lajmi, Dhouha (Neophilologica, 2007)
There exist in French some verbal sequences which are used to “actualize” nominal predicates and which have a same role assigned with standard support verbs. These constructions have a problematic structuring insofar as they are plural or rather complexes from where their denomination “complex support verbs”. Our objective consists, in this article, to describe their double combinative: an intern combinative which assimilate them to frozen sequences and another external which has a similar syntactic and semantic operation with that of the standard support verbs. We will show through the description of a particular type of complex supports verbs, namely the passive complex support verbs, common properties of this verbs in French and Arabic languages. We will release, finally specificities of the Arabic passive complex support verbs.